Validity and reliability of the persian version of the chronic oral mucosal diseases questionnaire - Atena Shirzad; Ali Bijani; Mahsa Mehryari; Mina Motallebnejad; Saman Mohsenitavakoli (Babol University of Medical Sciences, 2018)
Background: Chronic oral mucosal disease questionnaire (COMDQ) is used to evaluate the quality of life in patients with chronic conditions of the oral mucosa. The aim of the present study was to evaluate the validity and reliability of the Persian version of this questionnaire. Methods: A total of 135 subjects were selected in two groups; group 1 consisted of 95 patients with chronic oral mucosal conditions, including recurrent aphthous stomatitis, oral lichen planus and pemphigus and mucous membrane pemphigoid and group 2 consisted of 40 patients with other oral diseases. The subjects completed the demographic data sheets and COMDQ and then underwent examinations to determine disease severity. After 14 days, the questionnaire was completed again by the group 1subjects only. Results: Cronbach’s α coefficient for COMDQ was estimated at 0.969 and the interclass correlation coefficient was estimated at 0.997. There was a significant relationship between the mean COMDQ scores and disease and pain severity. There was a clear correlation between the patients’ self-report about their general health and mean COMDQ scores and also between their opinions about their oral health and the mean COMDQ scores. Conclusions: The Persian version of COMDQ exhibited proper levels of reliability and validity. It is suggested that this questionnaire be used for the evaluation of the effect of treatment on the oral health-related quality of life (OHQoL).